Phenotypic and Genomic Characterization of ESBL- and AmpC-β-Lactamase-Producing Enterobacterales Isolates from Imported Healthy Reptiles - Franziska Unger; Tobias Eisenberg; Ellen Prenger-Berninghoff; Ursula Leidner; Torsten Semmler; Christa Ewers (Antibiotics)
Background/Objectives: Reptiles are known reservoirs for members of the Enterobacterales. We investigated antimicrobial resistance (AMR) patterns, the diversity of extended-spectrum-/AmpC-β-lactamases (ESBL/AmpC) genes and the genomic organization of the ESBL/AmpC producers. Methods: A total of 92 shipments with 184 feces, skin, and urinate samples of live healthy reptiles were obtained during border inspections at Europe’s most important airport for animal trade and screened for AMR bacteria by culture, antimicrobial susceptibility testing, and whole genome sequencing (WGS) of selected isolates. Results: In total, 668 Enterobacterales isolates with phenotypic evidence for extended-spectrum-/AmpC-β-lactamases (ESBL/AmpC) were obtained, from which Klebsiella (n = 181), Citrobacter (n = 131), Escherichia coli (n = 116), Salmonella (n = 69), and Enterobacter (n = 52) represented the most common groups (other genera (n = 119)). Seventy-nine isolates grew also on cefotaxime agar and were confirmed as ESBL (n = 39) or AmpC (n = 39) producers based on WGS data with respective genes localized on chromosomes or plasmids. Isolates of E. coli contained the most diverse set of ESBL genes (n = 29), followed by Klebsiella (n = 9), Citrobacter, and Enterobacter (each n = 1). Contrarily, AmpC genes were detected in E. coli and Citrobacter (n = 13 each), followed by Enterobacter (n = 12) and Klebsiella (n = 4). Isolates of Salmonella with ESBL/AmpC genes were not found, but all genera contained a variety of additional AMR phenotypes and/or genotypes. MLST revealed 36, 13, 10, and nine different STs in E. coli, Klebsiella, Citrobacter, and Enterobacter, respectively. Conclusions: A significant fraction of the studied Enterobacterales isolates possessed acquired AMR genes, including some high-risk clones. All isolates were obtained from selective media and also wild-caught animals carried many AMR genes. Assignment of AMR to harvesting modes was not possible.